The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1117/12.724889
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-induced damage of multilayer coatings in EUVL

Abstract: A Particle-in-Cell Monte Carlo model is used to simulate extreme ultraviolet driven plasma. In an extreme ultraviolet lithography tool, photons of a pulsed discharge source will ionize a low pressure argon gas by photoionization. Together with the photoelectric effect, this results in a strongly time dependent and low density plasma, which is potentially dangerous to the optical elements, the collector in particular. Plasma sheaths will develop and ions are accelerated towards the collector, which might lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The PIC method allows for accommodating an arbitrary shape of the energy distribution function against reasonable computational costs. To the authors' knowledge, the first PIC modelling of EUV-induced plasmas was performed by Wieggers, Goedheer and Louis [20]. These authors used one-dimensional (1D) particle-in-cell codes and estimated the damage to a multilayer mirror (MLM) due to physical sputtering.…”
Section: Recent Numerical Work On Euv-induced Bulk Plasmasmentioning
confidence: 99%
“…The PIC method allows for accommodating an arbitrary shape of the energy distribution function against reasonable computational costs. To the authors' knowledge, the first PIC modelling of EUV-induced plasmas was performed by Wieggers, Goedheer and Louis [20]. These authors used one-dimensional (1D) particle-in-cell codes and estimated the damage to a multilayer mirror (MLM) due to physical sputtering.…”
Section: Recent Numerical Work On Euv-induced Bulk Plasmasmentioning
confidence: 99%
“…In recent years, many researchers have dedicated their work to understanding the dynamic behavior of EUVinduced plasma and its impact on the performance of EUV lithography equipment. For example, van der Velden et al [4] numerically studied the characteristics of EUV-induced argon (Ar) plasma near multilayer mirrors. Their results suggested that the energy of Ar + ions may exceed the physical sputtering threshold of the mirror surface, and potentially cause damage to the mirror.…”
Section: Introductionmentioning
confidence: 99%
“…17 EUV induced plasmas have been considered in 1D with argon as background gas [22], [23]. We did not use this work as a starting point, because we need to deal with hydrogen in 2D.…”
Section: "Why a New Code"mentioning
confidence: 99%